Emotion the gatekeeper to performance : the mind/body connection - National Professional Resources (1Port Chester, NY. : National Professional Resources, 1999)
Discover the relationship between performance and mind/body
Executive producer, Robert M. Hanson ; associate producer, angela T. Hanson
Featuring, Candace B. Pert
Keywords: Mind and body; Emotions; Self-actualization (Psychology).